ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PENERAPAN KONSERVATISME DALAM AKUNTANSI PADA PERUSAHAAN SUB SEKTOR OTOMOTIF DAN KOMPONEN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Replita, Replita; Windari, Windari; Hasibuan, Lismawati; Maha, Ninka Mala (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
The purpose of this study is to test and analyze influence Managerial Ownership Structure, Public Ownership Structure, Structure Institutional Ownership, Company Size, Partial good leverage and simultaneously against Conservatism in Sub-Sector Companies Automotive and Components on the Indonesia Stock Exchange (IDX). Research population is a manufacturing company listed on the Indonesia Stock Exchange Selection of research samples using purposive sampling method with predetermined criteria. Based on those criteria, obtained a sample of 10 companies over a three-year period Observation. The data used is secondary data. Research using multiple linear regression analysis and hypothesis testing using test t, F test, and coefficient of determination test. The results showed that the factors that influenced a significant positive to accounting conservatism is the ownership structure managerial, public ownership structure, and company size. While the factor others such as institutional ownership structure and leverage have no effect significant to accounting conservatism.